2016
DOI: 10.1016/j.neuron.2016.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Protein Synthesis Is Required for Long-Term Plasticity of GABA Release

Abstract: Summary Long-term changes of neurotransmitter release are critical for proper brain function. However, the molecular mechanisms underlying these changes are poorly understood. While protein synthesis is crucial for the consolidation of postsynaptic plasticity, whether and how protein synthesis regulates presynaptic plasticity in the mature mammalian brain remains unclear. Here, using paired whole-cell recordings in rodent hippocampal slices, we report that presynaptic protein synthesis is required for long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
185
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(194 citation statements)
references
References 66 publications
9
185
0
Order By: Relevance
“…Thus, while local production of β-catenin is required only during the first steps of presynapse assembly and does not generate the bulk of presynaptic β-catenin protein, SNAP25 synthesis persist at least until 12 hours after initiation of presynapse formation, it generates a substantial amount of synaptic SNAP25 proteins, and it continues to be required even in established synapses, as demonstrated by the effect of axonal SNAP25 mRNA knockdown on synaptic vesicle release. A recent translatome analysis of retinal ganglion cells axons identified SNAP25 as highly expressed not only in developing but also mature axons (Shigeoka et al, 2016), and inhibition of protein synthesis at established presynaptic terminals deregulates GABA release (Younts et al, 2016). The stability of SNAP25 at presynapses is controlled by activity induced ubiquitination and proteasome-dependent degradation (Sheehan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, while local production of β-catenin is required only during the first steps of presynapse assembly and does not generate the bulk of presynaptic β-catenin protein, SNAP25 synthesis persist at least until 12 hours after initiation of presynapse formation, it generates a substantial amount of synaptic SNAP25 proteins, and it continues to be required even in established synapses, as demonstrated by the effect of axonal SNAP25 mRNA knockdown on synaptic vesicle release. A recent translatome analysis of retinal ganglion cells axons identified SNAP25 as highly expressed not only in developing but also mature axons (Shigeoka et al, 2016), and inhibition of protein synthesis at established presynaptic terminals deregulates GABA release (Younts et al, 2016). The stability of SNAP25 at presynapses is controlled by activity induced ubiquitination and proteasome-dependent degradation (Sheehan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts coding for several presynaptic proteins have been found in developing cortical axons (Taylor et al, 2009), and in Aplysia, protein synthesis is required for the formation of presynapses (Schacher and Wu, 2002). Recently, the importance of presynaptic protein synthesis in the control of neurotransmitter release was reported for the mature mammalian brain (Younts et al, 2016), but the role of local translation in the formation of presynapses remains poorly understood. Specifically, it is unknown whether axonal protein synthesis is required for the assembly of presynaptic terminals.…”
Section: Introductionmentioning
confidence: 99%
“…Several effectors downstream CB 1 have been identified, including PKA signaling, the active zone protein RIM1α, and voltage-gated calcium channels, although alternative downstream CB 1 signaling cascades (Njoo et al, 2015; Roland et al, 2014) leading to structural changes could also be involved. A recent study demonstrated that activation of CB 1 receptors stimulates protein synthesis in axon terminals to induce eCB-iLTD in the hippocampus (Younts et al, 2016). In addition, CB 1 activation enhances protein translation via mTOR signaling.…”
Section: Ecb Signaling At Hippocampal and Neocortical Synapsesmentioning
confidence: 99%
“…In addition to CB1 receptor signaling, eCB-LTD also requires increased intracellular calcium at the presynaptic terminal – typically elicited by repetitive depolarization (Heifets et al, 2008; Mato et al, 2008) – and inhibition of AC by CB1-linked Ga i/o signaling, leading to inhibition of protein kinase A and decreased phosphorylation of substrates such as the vesicle-associated Rim1 proteins (Chevaleyre et al, 2007; Mato et al, 2008). Increased protein translation at the presynaptic terminal is also necessary for eCB-LTD expression (Yin et al, 2006, Younts et al, 2016). The net result of these processes is a long-lasting decrease in the probability of presynaptic vesicle fusion and neurotransmitter release at most synapses (but see Carey et al, 2011).…”
Section: Brief Primer To Endocannabinoid Signalingmentioning
confidence: 99%